A Improving the Students’ Ability to Write Descriptive Text through Instagram Captions - Iqlima, Ilva Yutika (Native: Journal of English Teaching and Learning, 2023)
Social media can help students and teachers to share files and to make online collaboration wirelessly. The teaching media for writing must be creative to make the students find many fun things during their writing class. This study aimed to analyze the improvement of using social media in academics in terms of writing skills in descriptive text and to analyze the students’ ability to learn to write descriptive text. This research was conducted with a qualitative approach with a case study. The observation, test, questionnaire, and interview were used in collecting the data. The participants of this research were 30 students of X IPA in SMA Muhammadiyah Rancaekek. The result showed that Instagram caption can help their writing process, and enhance their writing skill. Therefore, this research conclusion showed students had a good impact on their learning writing process and had a positive perception of enhancing their writing skills.